PCR validation of predicted virulence factors in a collection of Xanthomonas campestris (pv. musacearum and vascolurum) strains - Wasukira, Arthur; Tusiime, Geoffrey; Kubiriba, Jerome (African Journal of Biotechnology, 2017)
Bacterial plant pathogens belonging to the Xanthomonas genus are adapted to their host plants and are not known to colonize other environments. Xanthomonas colonize host parts such as leaves, stems and roots before entering vascular tissues and engaging in an invasive pathogenic phase. These bacterial strains have evolved strategies to adapt to life in this environment. The host-pathogen interactions of Xanthomonas vasicola (Xv) need to be well understood to properly map the target genes in the host and pathogen so as to understand the mechanism of resistance. Genotypic characterization, based on the analysis of restriction fragment length polymorphism of virulence factor fragment products was performed on members of the X. vasicola pv. musacearum (Xcm) and X. vasicola pv. vasculorum (Xvv) from varying geographical locations. The study showed that Xcm and Xvv are different from each other based on amplification of virulence factors within fragments of their DNA. Bacterial strains of similar species can have unique Type four pili (Tfp) and Tfp pilus assembly protein PilF a fimbrial biogenesis protein was amplified in all Xanthomonas strains except NCPPB1131 only. Type III effector protein RipT was confirmed to be present in all strains of Xcm and Xvv but not NCPPB1131 and NCPPB1132. All the Xcm and Xvv strains under test yielded bands of type III effector HopAF1 except Xvv206, NCPPB1131 and NCPPB1132. YopJ type III secretion system effector protein hybridizes in DNA of all Xcm strains tested but not in NCPPB1131 or NCPPB1132. This study confirmed the predicted presence or absence of virulence factors especially effectors across bacterial strains and within strains of the same species and other clusters conserved in gram negative bacteria.
Keywords: Banana; Effectors; Pathogen-host; Xanthomonas wilt; Xanthomonas campestris; Xanthomonas vasicola